Perbandingan Kinerja Oven Konvensional Dengan Oven Semiotomatis Pada Pemanggangan Ubi Madu (Ipomoea batatas) Pasrujambe Lumajang - Arif Budiman Tito (Fakultas Teknologi Pertanian, 2025)
The process of roasting honey sweet potato (Ipomoea batatas) from Pasrujambe Lumajang generally still uses a conventional oven that has limitations in temperature regulation and product turning, so a semiautomatic oven was developed with an automatic temperature control system and a safer and more efficient turning mechanism. This study compared the performance of conventional ovens and semiautomatic ovens based on energy consumption, temperature distribution. Tests were carried out by experimental method using scales and watt meters to measure energy consumption, thermocouple sensors for temperature measurement and Autodesk Computational Fluid Dynamics (CFD) for temperature visualization. The results showed that the semiautomatic oven was more energy efficient, with a consumption of 0.26 kg/hour of gas and 39.21 Wh of electricity, which is equivalent to a cost of approximately Rp1,949.8 per hour, compared to the conventional oven that consumed 0.59 kg/hour of gas, at a cost of approximately Rp4,327 per hour. The semi-automatic oven also showed better temperature stability, although the temperature distribution was less even.
Entry oleh Arif 2026 Maret 16
Keywords: Semiautomatic Oven; Conventional Oven; Honey Sweet Potato; Energy Consumption; Temperature Distribution